The Ratio Equilibria and the Core of the Voting Game G(N, W) in a Public Goods Economy - Kaneko, Mamoru (Econometrica, 1977)
[In Kaneko [6] we considered the relationship between the ratio equilibria and the core of the voting game G(N, W,r), in which a fixed ratio is given. In this paper we present a new voting game G(N, W) in which no fixed ratio is given, and consider the relationship between the ratio equilibria and the core of G(N, W). We prove that the core of G(N, W) coincides with the ratio equilibria.]